Aşağı Fırat Havzası Folklorunda Hayvanlar ile İlgili İnanışlar - Yüksel, Erhan; Özen, Rahşan (Mersin University, 2013)
Bu araştırmada, bilinen tarihin önemli yerleşim merkezlerinin başında gelen ve birçok uygarlığa ev sahipliği yaptığı için halk bilimi açısından büyük önem taşıyan Aşağı Fırat Havzasında, hayvanlar ile ilgili inanışların derlenerek literatüre kazandırılması amaçlandı. Bu amaçla Aşağı Fırat Havzasında yer alan Adıyaman, Elazığ, Malatya, Şanlıurfa illeri ile Gaziantep’in Nizip ilçesinde toplam 123 kişiyle yüz yüze görüşme yapıldı. Elde edilen bulgular “içerik analizi” yöntemiyle değerlendirildi. Çalışmada, Aşağı Fırat Havzasında horoz, güvercin, koyun, leylek ve kır atın uğurlu; keçi, kedi, alaca sığır, siyah katır, eşek ve tavşanının uğursuz; köpek, baykuş ve tilkinin de kimi zaman uğurlu kimi zaman da uğursuz hayvanlar olarak kabul edildiği saptandı. Ayrıca, yeni doğum yapan hayvanların eşinin (plasenta), hayvanın sütünün bol olacağı inancıyla incir ağacına asıldığı veya aynı beklentiyle akarsuya atıldığı; nazardan korunmak için ev ve ahırlara, at, büyükbaş ve küçükbaş hayvanların kafatası ile kaplumbağa kabuğunun asıldığı şeklinde bulgulara ulaşıldı. Sonuç olarak, Aşağı Fırat Havzasında, hayvanlarla ilgili inanışlar açısından zengin folklorik uygulamalara rastlandığı ve yörede saptanan inanışların birçoğunun Anadolu’nun farklı bölgelerindekilere benzer olduğu saptanmıştır

As is known, folk beliefs encompasses values that are widely maintained by the folk and passed down to future generations. Animals, as an inseparable part of the life of mankind, have earned an important place in folk beliefs, and these beliefs also constitute a major component of veterinary folklore. This study was aimed at the compilation and introduction to scientific literature of the folk beliefs on animals in the lower Euphrates basin, a major settlement area of common history, which has been home to several civilizations, and thus, is an area of great significance for folklore. For this purpose, in total 123 persons, residing in the lower Euphrates basin in the Adıyaman, Elazığ, Malatya and Şanlıurfa provinces and the Nizip district of Gaziantep province, were interviewed in person. The findings obtained were assessed using the “content analysis” method. The study revealed that, in the lower Euphrates basin, the rooster, pigeon, sheep, stork and dapplegrey horse are considered to bring good luck; whilst the goat, cat, multi-colored cattle, black mule, donkey and rabbit are considered to bring bad luck. On the other hand, the findings obtained demonstrated that the dog, owl and fox are sometimes considered to bring good luck and sometimes to bring bad luck. Furthermore, it was determined that the placenta of newly giving birth animals is either hung on the branch of a fig tree or thrown into the river, in the belief that this would increase the milk yield of lactating animals, and it was ascertained that the skull of horses, cattle, sheep and goats as well as tortoise shells are hung on the walls of houses and stables, in the belief that this would protect the people and animals from the evil eye. In conclusion, rich folkloric elements related to folk beliefs on animals were observed in the lower Euphrates basin and the beliefs of this region were found to be similar to those maintained in the different regions of Anatolia.
Folk Beliefs on Animals in the Lower Euphrates Basin